Consolidation in times of overcapacity: strategic alliances vs. mergers and acquisitions in the liner shipping industry - Rondini, Matteo (2018)
As the world has witnessed in the recent past, the economic environment surrounding global trade has become increasingly dynamic and uncertain, with sudden and unexpected crises, trade imbalances and downturns of various nature. A sizeable number of companies have been forced out of business across different industries due to their lack of ability to continuously adapt to a rapidly changing environment; perhaps one of the most interesting industries to analyse in this context of uncertainty is that of the Liner Shipping, which has particularly suffered in the past 5 years. Indeed, the market for freight transportation of goods has been hit by a chronic issue of overcapacity, which carriers have failed to keep under control for different reasons that will be analysed later in this work. Many liners have entered into strategic alliances to try and reduce the losses triggered by increasing competition in the market, as well as by a growing number of available vessels that caused freight prices to drop significantly; others have recurred to mergers and acquisitions of competitors, in an effort to reduce the overall capacity of the market although, as we will see, the desired effects have been slow to appear. In this paper, I will conduct an in-depth analysis of the economic factors responsible for this excess capacity that has been so harmful to the shipping industry, but I will also develop an understanding of the effects that both strategic alliances and M&As have produced on the competitive environment; this will serve as a basis to outline possible future trends and develop some insights for the industry decision-makers. Starting with a literature review to present the main research question and hypotheses, I will mostly base my research on a quantitative methodology, using secondary data on freight rates variations over time and other economic indicators, and analysing them in order to verify the research question.